Furan Derivatives Recent Advances and Applications - Khan, Anish; Muzibur Rahman, Mohammed; Ramesh, M.; Ahmad Khan, Salman; Mohammed Ahmed Asiri, Abdullah (IntechOpen, 2022)
The modern world is moving towards sustainable development and furan is a key material in this transition. Furan is processed from furfural, which is an organic compound obtained from biomass feedstock. Thus, furan is a green and environmentally friendly material. It is used to produce pharmaceuticals, resin, agrochemicals, and lacquers. It is a key starting material for a variety of industries for the preparation of many useful products. This book presents comprehensive information on furan and its derivatives.